Antibody-dependent cellular cytotoxicity-inducing antibodies enhance the natural killer cell anti-cancer response against patient-derived pancreatic cancer organoids - Beelen, Nicky A.; Aberle, Merel R.; Bruno, Virginia; Olde Damink, Steven W. M.; Bos, Gerard M. J.; Rensen, Sander S.; Wieten, Lotte (Frontiers in Immunology, 2023)
Pancreatic cancer is associated with poor prognosis, and limited treatment options are available for the majority of patients. Natural killer (NK) cells in combination with antibodies inducing antibody-dependent cell-mediated cytotoxicity (ADCC) could be a highly effective new therapeutic option in pancreatic cancer. Accurate predictive preclinical models are needed to develop successful NK cell immunotherapy. Tumor organoids, in vitro 3D organ-like structures that retain important pathophysiological characteristics of the in vivo tumor, may provide such a model. In the current study, we assessed the cytotoxic potential of adoptive NK cells against human pancreatic cancer organoids. We hypothesized that NK cell anti-tumor responses could be enhanced by including ADCC-triggering antibodies. We performed cytotoxicity assays with healthy donor-derived IL-2-activated NK cells and pancreatic cancer organoids from four patients. A 3D cytotoxicity assay using live-cell-imaging was developed and enabled real-time assessment of the response. We show that NK cells migrate to and target pancreatic cancer organoids, resulting in an increased organoid death at the 5:1 effector-to-target cell (E:T) ratio, compared to the no NK cell controls (average fold change from baseline of 2.2±0.9 vs 1.4±0.6). After 24-hours of co-culture, the apoptotic signal within organoids plateaued, after which organoid 2D growth increased. Organoids from 2 out of 4 patients were sensitive to NK cells while organoids from the other two patients were relatively resistant, indicating patient-specific heterogeneity among organoid cultures. The ADCC-inducing antibodies avelumab (anti-PD-L1) and trastuzumab (anti-HER2) increased NK cell-induced organoid cell death, which was highest at the 5:1 E:T-ratios (average fold change from baseline of 3.5±1.0 and 4.5±1.8, respectively). Moreover, combination therapy with avelumab and trastuzumab resulted in complete disintegration of organoids. Finally, inclusion of ADCC-inducing antibodies was able to overcome resistance in NK-organoid combinations with low or no kill. These results support the use of organoids as a relevant and personalized model to study the anti-tumor response of NK cells in vitro and the potential of ADCC-inducing antibodies to enhance NK cell effector function.